Extracellular vesicles in blood, milk and body fluids of the female and male urogenital tract and with special regard to reproduction - Foster, B. P.; Balassa, T.; Benen, T. D.; Dominovic, M.; Elmadjian, G. K.; Florova, V.; Fransolet, M. D.; Kestlerova, A.; Kmiecik, G.; Kostadinova, I. A.; Kyvelidou, C.; Meggyes, M.; et al. (Critical reviews in clinical laboratory sciences, 2016)
Extracellular vesicles (EVs) are released from almost all cells and tissues. They are able to transport substances (e.g. proteins, RNA or DNA) at higher concentrations than in their environment and may adhere in a receptor-controlled manner to specific cells or tissues in order to release their content into the respective target structure. Blood contains high concentrations of EVs mainly derived from platelets, and, at a smaller amount, from erythrocytes. The female and male reproductive tracts produce EVs which may be associated with fertility or infertility and are released into body fluids and mucosas of the urogenital organs. In this review, the currently relevant detection methods are presented and critically compared. During pregnancy, placenta-derived EVs are dynamically detectable in peripheral blood with changing profiles depending upon progress of pregnancy and different pregnancy-associated pathologies, such as preeclampsia. EVs offer novel non-invasive diagnostic tools which may reflect the situation of the placenta and the foetus. EVs in urine have the potential of reflecting urogenital diseases including cancers of the neighbouring organs. Several methods for detection, quantification and phenotyping of EVs have been established, which include electron microscopy, flow cytometry, ELISA-like methods, Western blotting and analyses based on Brownian motion. This review article summarises the current knowledge about EVs in blood and cord blood, in the different compartments of the male and female reproductive tracts, in trophoblast cells from normal and pre-eclamptic pregnancies, in placenta ex vivo perfusate, in the amniotic fluid, and in breast milk, as well as their potential effects on natural killer cells as possible targets.
Gesehen am 03.06.2020